Corneal-Reflection Eye-Tracking Technique for the Assessment of Horizontal Sound Localization Accuracy from 6 Months of Age. Issue 2 (March 2016) - Asp, Filip; Olofsson, Åke; Berninger, Erik
Abstract : Objectives: The evaluation of sound localization accuracy (SLA) requires precise behavioral responses from the listener. Such responses are not always possible to elicit in infants and young children, and procedures for the assessment of SLA are time consuming. The aim of this study was to develop a fast, valid, and objective method for the assessment of SLA from 6 months of age. To this end, pupil positions toward spatially distributed continuous auditory and visual stimuli were recorded. Design: Twelve children (29 to 157 weeks of age) who passed the universal newborn hearing screening and eight adults (18 to 40 years of age) who had pure-tone thresholds ⩽20 dB HL in both ears participated in this study. Horizontal SLA was measured in a sound field with 12 loudspeaker/display (LD)-pairs placed in an audiological test room at 10 degrees intervals in the frontal horizontal plane (±55 degrees azimuth). An ongoing auditory-visual stimulus was presented at 63 dB SPL(A) and shifted to randomized loudspeakers simultaneously with pauses of the visual stimulus. The visual stimulus was automatically reintroduced at the azimuth of the sounding loudspeaker after a sound-only period of 1.6 sec. A corneal-reflection eye-tracking technique allowed the acquisition of the subjects' pupil positions relative to the LD-pairs. The perceived azimuth was defined as the median of the intersections between gaze and LD-pairs during the final 500 msec of the sound-only period. Overall SLA was quantified by an Error Index (EI), where EI = 0 corresponded to perfect match between perceived and presented azimuths, whereas EI = 1 corresponded to chance. Results: SLA was rapidly measured in children (mean = 168 sec, n = 12) and adults (mean = 162 sec, n = 8). Visual inspection of gaze data indicated that gaze shifts occurred in sound-only periods. The medians of the perceived sound-source azimuths either coincided with the presenting sound-source azimuth or were offset by a maximum of 20 degrees in children. In contrast, adults revealed a perfect match from −55 to 55 degrees, except at 15 degrees azimuth (median = 20 degrees), with 9/12 of the quartile ranges = 0 degrees. Children showed a mean (SD) EI of 0.42 (0.17), which was significantly higher than that in adults ( p < 0.0001). However, children revealed a distinct age-related EI improvement of 16 percentage points per year ( r = −0.68, p = 0.015, n = 12), suggesting an ongoing maturation of SLA in the studied age range (29 to 157 weeks). The eight adults showed high SLA and high reliability as demonstrated by the low mean (SD) EI (0.054 [0.021]) and the low variability in test–retest differences (95% confidence interval = −0.020 to 0.046). Conclusions: Corneal-reflection eye-tracking provides an objective and fast assessment of horizontal SLA from about 6 months of age and may enable gaze to be used as an objective measure for sound localization in this age group. Infant SLA is immature and improvements are related to increasing age. Adults show high overall SLA and low intra- and intersubject variability in SLA. The technique may be used as a clinical tool for the evaluation of very early intervention in a young, preverbal population and throughout the life span. Abstract : We measured infant and adult horizontal sound localization accuracy by recording participants' pupil positions in relation to spatially distributed continuous auditory and visual stimuli. We found gaze to be a fast, precise, and objective method for sound localization measurements in infants and adults. A distinct effect of age on sound localization accuracy was revealed in infants. Adults showed high overall localization accuracy and low intra- and intersubject variability.Supplemental Digital Content is available in the text.